2006
DOI: 10.1094/pd-90-0279
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Silicate Reduces Postharvest Decay on Hami Melons: Induced Resistance and Fungistatic Effects

Abstract: The effect of sodium silicate (Si) for control of decay was tested in Hami melons (Cucumis melo L. var. inodorus Jacq.). Si significantly inhibited mycelial growth of Alternaria alternata, Fusarium semitectum, and Trichothecium roseum in vitro. Si at 100 mM was more effective than Si at 25 or 50 mM at controlling the diseases caused by the three pathogens, whereas Si at 200 mM was phytotoxic. Si treatments applied at 100 mM pre-inoculation with T. roseum had lower decay incidence and severity than treatments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 31 publications
7
42
2
4
Order By: Relevance
“…Regarding Cryptococcus laurentii-sweet cherry interaction, increased polyphenol oxidase activity reduced disease severity in fruit treated with 1% silicon (Qin and Tian, 2005). Enhanced peroxidase activity in melon plants treated with sodium silicate decreased incidence of pink rot caused by Trichothecium roseum (Bi et al, 2006). Increased rice resistance due to silicon treatment against the brown spot pathogen (Bipolaris oryzae) seems to be the result of higher levels of chitinase and peroxidase (Dallagnol et al, 2011).…”
Section: Defense-related Enzymesmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding Cryptococcus laurentii-sweet cherry interaction, increased polyphenol oxidase activity reduced disease severity in fruit treated with 1% silicon (Qin and Tian, 2005). Enhanced peroxidase activity in melon plants treated with sodium silicate decreased incidence of pink rot caused by Trichothecium roseum (Bi et al, 2006). Increased rice resistance due to silicon treatment against the brown spot pathogen (Bipolaris oryzae) seems to be the result of higher levels of chitinase and peroxidase (Dallagnol et al, 2011).…”
Section: Defense-related Enzymesmentioning
confidence: 93%
“…Also, the potassium silicate concentrations used by Bekker et al (2006) were 50 to 60 times higher than those in Shen's et al (2010) study. Moreoever, these concentrations (Bekker et al, 2006;Bi et al, 2006) are unrealistic for fi eld use because the high pH of the resulting potassium silicate solutions could cause phytotoxicity. Shen et al (2010) concluded that the reduction in fungal diseases following treatment of fi eld plants with silicon is probably not due to the fungistatic eff ects of silicon, but to other biochemical and physical mechanisms mentioned previously.…”
Section: In Vitro Inhibition Of Fungal Pathogens By Soluble Siliconmentioning
confidence: 99%
“…Ce produit est présenté comme étant un biopesticide à triple activité : fongicide, insecticide et arachnicide. Le concept d'une induction de résistance par la silice a largement été confirmé au cours des dernières années, qu'il s'agisse du melon (Cucumis melo L.) (Bi et al 2006), de la cerise (Prunus avium L.) (Qin et Tian 2005) ou de la fraise (Kanto et al 2007). …”
Section: Le Messengerunclassified
“…Some treatments have been found to improve disease resistance in Hami melon. For example, the application of natamycin in combination with bilayer films consisting of chitosan and polyethylene wax have been shown to inhibit the growth of Alternaria alternate and Fusarium semitectum on the melon surface (Cong et al, 2007), while sodium silicate treatment has been found to inhibit the growth of Trichothecium roseum (Bi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%